Lichen Planopilaris Pemphigoides: A Novel Bullous Dermatosis Due to Programmed Cell Death Protein-1 Inhibitor Therapy. (20th April 2023) - Liu, Shuo S.; Howard, Tara; Fattah, Yasmin H.; Adams, Amy; Hanly, Andrew J.; Karai, Laszlo J.
Abstract: Lichen planus pemphigoides (LPPemph), apart from bullous pemphigoid, is a rare bullous dermatosis that can be induced by programmed cell death protein-1 (PD-1)/PD ligand 1 (PD-L1) inhibitors. The primary location of PD-1/PD-L1 inhibitor–induced LPPemph has previously only been reported at the nonfollicular dermal–epidermal junction. We present a case of nivolumab-induced LPPemph with an intense perifollicular lichenoid reaction, prominent multifocal perifollicular clefting, which in addition, was also accompanied by linear IgG and C3 immunofluorescence deposits along the dermal–epidermal junction as well as demonstrating a perifollicular pattern. Intriguingly, the serological study of BP180 and BP230 antibodies was negative, suggesting the presence of additional novel antibodies, which primarily favor hair follicles and may contribute to the pathogenesis. Therefore, we consider this entity a novel variant of PD-1/PD-L1 inhibitor–induced bullous dermatosis. To the best of our knowledge, this is the first report that highlights perifollicular bullae accompanied by immunofluorescence findings in a PD-1/PD-L1 inhibitor–induced lesion. We propose a new immunotherapy associated entity, lichen planopilaris pemphigoides, and emphasize the significance of perifollicular changes in the pathogenesis.